Myrtaceae from lowland Atlantic Forest areas in the State of Pernambuco, Northeastern Brazil - Amorim, Bruno S.; Alves, Marccus (Phytotaxa, 2015)
The lowland Atlantic Forest in the State of Pernambuco (northeastern Brazil) is a mosaic of forest fragments with high biological importance and a priority for biological inventories. Myrtaceae is represented by 38 species; with 12 species each, Eugenia and Myrcia are the richest genera, followed by Psidium with 4 species, Myrciaria with 3 species, Campomanesia and Marlierea with 2 species each and Calyptranthes, Gomidesia and Plinia with one species each. More than sixty percent of all species found in this inventory are endemic to the Atlantic Forest, one of them is a new record for northeastern Brazil (Myrciaria glazioviana); five are new records for the northern part of the Atlantic Forest (Eugenia brevistyla; Marlierea excoriata; M. tomentosa; Myrcia insularis and M. tenuivenosa) and one of them is a new record for the State of Pernambuco (Eugenia luschnathiana). An identification key, comments and illustrations of diagnostic characters of the species are provided.